Bipolar Electrochemistry. Issue 40 (10th July 2013) - Fosdick, Stephen E.; Knust, Kyle N.; Scida, Karen; Crooks, Richard M.
Abstract A bipolar electrode (BPE) is an electrically conductive material that promotes electrochemical reactions at its extremities (poles) even in the absence of a direct ohmic contact. More specifically, when sufficient voltage is applied to an electrolyte solution in which a BPE is immersed, the potential difference between the BPE and the solution drives oxidation and reduction reactions. Because no direct electrical connection is required to activate redox reactions, large arrays of electrodes can be controlled with just a single DC power supply or even a battery. The wireless aspect of BPEs also makes it possible to electrosynthesize and screen novel materials for a wide variety of applications. Finally, bipolar electrochemistry enables mobile electrodes, dubbed microswimmers, that are able to move freely in solution.